Phosphorus-doped graphene aerogel as self-supported electrocatalyst for CO₂ -to-ethanol conversion - Yang, Fangqi (2023)
Electrochemical reduction of carbon dioxide (CO2 ) to ethanol is a promising strategy for global warming mitigation and resource utilization. However, due to the intricacy of C─C coupling and multiple proton-electron transfers, CO2 -to-ethanol conversion remains a great challenge with low activity and selectivity. Herein, it is reported a P-doped graphene aerogel as a self-supporting electrocatalyst for CO2 reduction to ethanol. High ethanol Faradaic efficiency (FE) of 48.7% and long stability of 70 h are achieved at -0.8 VRHE . Meanwhile, an outstanding ethanol yield of 14.62 µmol h-1 cm-2 can be obtained, outperforming most reported electrocatalysts. In situ Raman spectra indicate the important role of adsorbed *CO intermediates in CO2 -to-ethanol conversion. Furthermore, the possible active sites and optimal pathway for ethanol formation are revealed by density functional theory calculations. The graphene zigzag edges with P doping enhance the adsorption of *CO intermediate and increase the coverage of *CO on the catalyst surface, which facilitates the *CO dimerization and boosts the EtOH formation. In addition, the hierarchical pore structure of P-doped graphene aerogels exposes abundant active sites and facilitates mass/charge transfer. This work provides inventive insight into designing metal-free catalysts for liquid products from CO2 electroreduction.